DAMPAK KONFLIK SOSIAL BURUH BONGKAR MUAT PELABUHAN NUSANTARA KOTA PAREPARE - Pallawagau, Saddam Taruna; Suhaeb, Firdaus W (Universitas Negeri Makassar, 2024)
This research was conducted to determine the impact of social conflicts among the dockworkers at the Parepare Nusantara Port. A qualitative approach was utilized to explore the effects of social conflicts among the dockworkers at the Parepare Nusantara Port. The research began with initial observations, followed by field visits to conduct direct interviews with the informants, along with the collection of documentation for reference. The researcher selected informants based on the criteria of being officially registered members of the dockworkers union at the Parepare Nusantara Port, consisting of both basic cargo laborers and baggage laborers. Data analysis techniques employed in this study included data collection, data reduction, data presentation, and drawing conclusions. The results of this research indicate that the impact of social conflicts among the dockworkers at the Parepare Nusantara Port comprises both functional and dysfunctional effects.